Pengaruh Brand Ambassador, Citra Merek dan Harga terhadap Keputusan Pembelian Produk Skincare Scarlett pada Masyarakat di Yogyakarta - Laura Sri Rejeki; Sri Ekanti Sabardini (Cakrawangsa Bisnis: Jurnal Ilmiah Mahasiswa, 2023)
This research aims to determine the influence of Brand Ambassador, Brand Image and Price on purchasing decisions for Scarlett Whitening brand skincare products. This research is a quantitative research conducted on Scarlett skincare consumers in Yogyakarta who are consumers of Scarlett products, a total of 75 people. Data were analyzed using multiple linear regression tests. Based on the results of data analysis, the results obtained were that Brand Ambassador had a significant positive effect on purchasing decisions with a significance value of 0.016 and a regression coefficient of 0.369. Brand image has a significant positive effect on purchasing decisions with a significance value of 0.021 and a regression coefficient value of 0.328. Price has a significant positive effect on purchasing decisions with a significance value of 0.01 and a regression coefficient value of 0.417. The coefficient of determination value shows that Brand Ambassador, Brand Image and Price have an influence of 72.6% on purchasing decisions.